Christian theology - Erickson, Millard J. (Grand Rapids, MI. : Baker Academic, 2013)
This influential textbook, now substantially updated and revised throughout, offers a comprehensive introduction to theology that is biblical, contemporary, moderate, and fair to various positions. The third edition takes into account feedback from professors and students and reflects current theological conversations, with added material on the atonement, justification, and divine foreknowledge.--Back cover.
Part 1. Studying God -- Part 2. Knowing God -- Part 3. What God is like -- Part 4. What God does -- Part 5. Humanity -- Part 6. Sin -- Part 7. The person of Christ -- Part 8. The work of Christ -- Part 9. The Holy Spirit -- Part 10. Salvation -- Part 11. The church -- Part 12. The last things.
First edition originally published as three volumes.
Includes bibliographical references and indexes.
Keywords: Theology, Doctrinal